Modelling biocontrol of invasive insects using WaspSim: A MATLAB simulation model - Oscar J. Cacho; Susan M. Hester (SoftwareX, 2023)
Globally, governments spend significant amounts of money attempting to prevent or mitigate the negative impacts of invasive species using different strategies, including classical biological control for species that are widespread in the landscape. Arriving at the point of biocontrol release requires significant investment of time and funds for research and testing, and success of the biocontrol agent is uncertain. We present a numerical model designed to assist in this process. The model is based on well-established equations of population growth and spread. Technical feasibility of a biocontrol programme is assessed based on the population parameters for the pest and biocontrol agent.